Processes of Lipid Peroxidation in Active-Motile Fraction of Human Spermatozoa, Isolated Prior to and After Cryopreservation - Podufaliy, V. V.; Cherkashina, I. V.; Kuchkov, I. N. (Problems of Cryobiology and Cryomedicine, 2008)
The content of malone dialdehyde, superoxide dismutase concentration and general antioxidative activity in active-motile fraction of human spermatozoa isolated prior to and after cryopreservation has been studied. It has been shown that the lipid peroxidation processes are more intensive in the samples isolated from ejaculates after thawing. The non-informativity of motility index for statement about the cryopreservation efficiency of active-motile fraction of spermatozoa has been established.